2019
DOI: 10.15640/ijgws.v7n2a13
|View full text |Cite
|
Sign up to set email alerts
|

The Nigerian Girl-Child and Sexual Abuse: The Plight of Victims in Bayelsa State Nigeria

Abstract: This study examined the effect of child sexual abuse on children in Yenagoa Local Government Area, Bayelsa State. Relevant literatures that deal on child sexual abuse were reviewed. Three research questions guided the study. Survey and semi-structured interview were the research design employed. Sample size for the study was 200 sexually abused children drawn from the ages between 0-17 years from Yenagoa Local Government Area of Bayelsa State. Yenagoa Local Government Area of Bayelsa was selected as the site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although the true burden of specific CSV in Nigeria is under‐represented, it is estimated to vary between 5% and 38% across different parts of the country (David et al, 2018; Ige & Fawole, 2011; Manyike et al, 2015). Available data indicate that the rate of sexual victimization for females was about five times the rate for males (Miller et al, 2018; Oluwatosin et al, 2019). Olusanya et al (1986) reported that children of elementary schools (aged 6–12 years) and adolescent girls (13–19 years) were the major victims of CSV, with 48.2% of reported cases over a 3‐year period occurring in children below 13 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Although the true burden of specific CSV in Nigeria is under‐represented, it is estimated to vary between 5% and 38% across different parts of the country (David et al, 2018; Ige & Fawole, 2011; Manyike et al, 2015). Available data indicate that the rate of sexual victimization for females was about five times the rate for males (Miller et al, 2018; Oluwatosin et al, 2019). Olusanya et al (1986) reported that children of elementary schools (aged 6–12 years) and adolescent girls (13–19 years) were the major victims of CSV, with 48.2% of reported cases over a 3‐year period occurring in children below 13 years old.…”
Section: Introductionmentioning
confidence: 99%